The Role of Financial Rations on Financial Distress Conditions in Transportation and Logistics Sector Companies at Indonesian Sharia Stock Index - Jannah, Safiratul; Priyadi, Ira Hasti (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2024)
Financial distress as an early warning signal of conditions that can lead to bankruptcy of a company. This study aims to examine the effect of financial ratios, namely liquidity, profitability, solvency, and activity on the financial distress of a company. The type of data used in this study is secondary data sourced from financial reports available at www.idx.com. The sample selection method is carried out by purposive sampling. The sample in this study was 44 Transportation and Logistics companies listed on the Indonesian Sharia Stock Index during the 2020-2023 period. The data testing tool used is multiple linear regression. The results of the F test analysis show that simultaneously, the variables of liquidity, profitability, solvency and activity have a significant effect on financial distress. Meanwhile, the results of the T test show that the variables of liquidity, profitability, solvency and activity have a significant effect on financial distress.